Distribution patterns of Dactylis glomerata subsp. slovenica (Poaceae) in the Ukrainian Carpathians - Bilonoha V.M.; Kyyak V.H.; Kozlovskyy V.I. (Ukrainian Botanical Journal)
Dactylis glomerata subsp. slovenica (Poaceae) is widespread in the Alps, Carpathians, Sudetes, the Giant Mountains (Krkonoše), and adjacent foothills. Some localities are also known in the northern Apennines, in the foothills of the French Pyrenees, Balkans, and the Caucasus, and occasionally outside the mentioned mountain systems in Poland, Germany, France, and Ukraine. In the Ukrainian Carpathians, it occurs in isolated populations in all main mountain ranges up to 1620 m above sea level, preferring tall herbaceous communities of the subalpine belt. Relatively strong restriction of D. glomerata subsp. slovenica to habitats with neutral or sub-acidic soils limits its advance on new areas in the Carpathians. The primary threats to the taxon are its geographical isolation, substrate requirements, and secondary successions associated with the expansion of Alnus alnobetula (A. viridis). Instead, reduced grazing or haymaking may have a positive impact on population size within existing localities or dispersal into areas with suitable soil conditions.